2007
DOI: 10.1103/physrevlett.99.037003
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Lattice Response at the Mott Transition in a Quasi-2D Organic Conductor

Abstract: Discontinuous changes of the lattice parameters at the Mott metal-insulator transition are detected by high-resolution dilatometry on deuterated crystals of the layered organic conductor kappa-(BEDT-TTF)(2)Cu[N(CN)(2)]Br. The uniaxial expansivities uncover a striking and unexpected anisotropy, notably a zero effect along the in-plane c axis along which the electronic interactions are relatively strong. A huge thermal expansion anomaly is observed near the end point of the first-order transition line enabling u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 28 publications
6
100
0
Order By: Relevance
“…Pressure dependent investigations on κ-Cl showed that the bandwidth-controlled Mott criticality involves critical fluctuations in charge, 58 spin, 59 and lattice. 60,61 Nothing like that is known for the spin-liquid compound κ-CN for the intermediate temperature range. While this issue can be clarified by further experimental studies, considerable theoretical work is required in order to describe the power-law behavior the dimer Mott insulator with a quantum spin-liquid state, in the low-frequency limit as well as in the far-infrared range.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure dependent investigations on κ-Cl showed that the bandwidth-controlled Mott criticality involves critical fluctuations in charge, 58 spin, 59 and lattice. 60,61 Nothing like that is known for the spin-liquid compound κ-CN for the intermediate temperature range. While this issue can be clarified by further experimental studies, considerable theoretical work is required in order to describe the power-law behavior the dimer Mott insulator with a quantum spin-liquid state, in the low-frequency limit as well as in the far-infrared range.…”
Section: Discussionmentioning
confidence: 99%
“…Such ferroelectricity induced by the electronic origin (electronic ferroelectricity [27][28][29]) is advantageous for high speed switching or modulation of dielectric properties. Figure 5c are Dimer-Mott (DM) insulators [30][31][32][33][34][35]. In κ-type ET salts, the ET layer has a unit comprising a pair of ET molecules (ET dimer).…”
Section: Introductionmentioning
confidence: 99%
“…The first-order character of the transition was confirmed by the observation of hysteresis in both R(T ) and relative length changes ( l/l) around T MI for another crystal. 7 The drop of the resistance at T c = 11.6 K, accompanied by a tiny kink (indicated by the arrow) in α b (T ), are signatures of a percolative SC in minor portions of the sample volume coexisting with the AFI state (see, e.g., Refs. 27 and 28).…”
Section: Resultsmentioning
confidence: 99%
“…24,26 Upon further cooling, a second anomaly around T P = 30 K is observed. This feature has been assigned to critical fluctuations associated with the second-order critical end point of the first-order line, 7,18 indicated by the solid triangle in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation